Africa Malaria Prevention Project - Zee, Harry van der (Homœopathic Links, 2016)
Malaria is the disease that has the biggest impact on the health and well-being of the peoples living in sub-Saharan Africa. Not only does malaria cause a lot of suffering and many deaths, the malaria miasm is also strongly connected to the inability to thrive and the frustration caused by that. The Africa Malaria Prevention Project (AMPP) aims at preventing malaria and treating its chronic effects by using PC240m—a genus epidemicus remedy designed to treat and prevent malaria. This article presents the first results and discusses a plan to roll out AMPP over all of sub-Saharan Africa.
Keywords: malaria; china officinalis; PC240m; prevention; homeoprophylaxis; Amma Resonance Healing Foundation; PC remedies